2020
DOI: 10.3390/jcm9051567
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Comprehensive Pulmonary Rehabilitation and its Maintenance in Patients with Idiopathic Pulmonary Fibrosis: A Randomized Controlled Trial

Abstract: The recommendation for pulmonary rehabilitation (PR) in idiopathic pulmonary fibrosis (IPF) is weak with low-quality evidence. Therefore, the aim of this study is to investigate short-term PR effects and their maintenance after a 3-month follow-up. Fifty-four IPF patients were randomized into a group receiving a 3-week comprehensive, inpatient PR (n = 34, FVC: 74 ± 19% pred.) or usual care (UC) (n = 17, FVC: 72 ± 20%pred.). Outcomes were measured at baseline (T1), after intervention (T2), and 3 months after T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(53 citation statements)
references
References 26 publications
1
47
0
5
Order By: Relevance
“…The literature search retrieved 12,214 articles, which were reviewed based on the title and abstract after discarding duplicates. Finally, 11 RCTs 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 met the inclusion criteria and were selected for this systematic review and meta-analysis ( fig 1 ), including a total sample of 637 participants. Excluded studies with reasons for exclusion are available in supplementary table S1 (available online only at http://www.archives-pmr.org/ ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature search retrieved 12,214 articles, which were reviewed based on the title and abstract after discarding duplicates. Finally, 11 RCTs 21 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 met the inclusion criteria and were selected for this systematic review and meta-analysis ( fig 1 ), including a total sample of 637 participants. Excluded studies with reasons for exclusion are available in supplementary table S1 (available online only at http://www.archives-pmr.org/ ).…”
Section: Resultsmentioning
confidence: 99%
“…As evaluated by Cochrane Collab ' f R T 18.2 % of the studies showed a high risk of bias, 31,37 72.7 % some concerns 21, 32-36, 38, 39 and 9,1 % a low risk of bias. 30 When studies were analysed by individual domains, 91% of them had shortcomings in the selection of the reported results domain 21,[31][32][33][34][35][36][37][38][39] (Supplementary Figure S1).…”
Section: Risk Of Biasmentioning
confidence: 99%
“…Currently, there is some evidence that suggests that the development of a fibrotic lung disease as an outcome of COIVD-19 is also a serious concern [33,34]. Since our study was not randomized and does not contain a COVID-19 control group without PR we would like to draw an indirect comparison by using a group of idiopathic pulmonary fibrosis (IPF) patients from a former study of our working group where the same outcome measures were assessed [35]. [36].…”
Section: Respiratory Parametersmentioning
confidence: 99%
“…Previous studies on PR in patients with IPF demonstrated a short-term effect on exercise capacity, dyspnea, and health-related quality of life [28]. However, few studies have evaluated the long-term effects of PR with inconsistent results [13][14][15][16]. Disease progression of IPF and acute respiratory events during and after PR might interfere with the long-term effect of PR [15].…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary rehabilitation (PR) is a comprehensive intervention, which mainly includes structured and supervised exercise training and education that has been clearly demonstrated to reduce dyspnea, increase exercise capacity, and improve health-related quality of life in individuals with chronic obstructive pulmonary disease (COPD) [10]. The effect of PR has been shown in patients with IPF [11][12][13]; however, these benefits are reportedly moderate and transient [14]. Although some long-term benefits have been reported [15,16], biases such as a low number of patients and intermingling of interstitial lung disease other than IPF could not be excluded.…”
Section: Introductionmentioning
confidence: 99%